2016
DOI: 10.1016/j.gore.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Primary leiomyosarcoma of the omentum presenting as an ovarian carcinoma, case report and review of the literature

Abstract: Primary omental leiomyosarcoma is a rare tumor. We report a case of successfully resected omental leiomyosarcoma whose presentation mimicked ovarian carcinoma. Symptoms of abdominal distension and discomfort that lasted 8 months followed by pain lead to a diagnosis of a large mass in the abdomen. Physical examination revealed a large, over 20 cm tumor, suspected to be of ovarian origin. A small amount of ascites was found on Computerized Tomography (CT) and ultrasound (US) scans. Total abdominal hysterectomy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The most common presenting symptom was abdominal mass followed by pain abdomen similar to the present case. Ascitis was also reported in few cases [2,3,6]. Our patient did not have ascitis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The most common presenting symptom was abdominal mass followed by pain abdomen similar to the present case. Ascitis was also reported in few cases [2,3,6]. Our patient did not have ascitis.…”
Section: Discussionsupporting
confidence: 59%
“…Most of these cases originated from the greater omentum. These tumors are generally seen in the middle age [2,3]. These tumors can mimic other tumors like gastrointestinal stromal tumors (GIST) due to their common origin from mesenchymal stem cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…Their etiological factors are still unknown. In a review of the literature, Fagkrezos et al reported 54 cases of extra-gastrointestinal stromal tumors [ 7 ], Barel et al reported 27 cases of leiomyosarcoma [ 8 ], and Hashimoto et al reported 19 cases of liposarcoma of the greater omentum [ 9 ]. According to these reports, the preoperative diagnosis of primary omental tumor is difficult because of its rarity, and thus, the diagnosis is usually made postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal leiomyosarcomas have been rarely reported since Hirota et al first described GISTs with c-kit mutations [1]. One such study is that by Barel et al who reported a case involving primary leiomyosarcoma of the omentum and reviewed 27 other cases previously published in the literature [4]. Moreover, lesser omental leiomyosarcomas are even more infrequent with only three cases being identified using a PubMed search with the keywords “lesser omentum” and “leiomyosarcoma.” However, all three reports did not include c-kit immunostaining, which would help distinguish leiomyosarcoma from GIST [57].…”
Section: Discussionmentioning
confidence: 99%
“…In a summary of 27 reports of primary omental leiomyosarcoma by Barel et al, 11 cases died during follow-up. Although the true prognosis for lesser omental leiomyosarcoma is unknown, it is likely to be poor [4]. Although the apparent prognosis for lesser omental leiomyosarcoma has remained unknown, the possibility of poor prognosis has been suggested.…”
Section: Discussionmentioning
confidence: 99%